Proceso de atención de enfermería en paciente de 19 años de edad con diagnóstico de sepsis puerperal en el Hospital Materno Infantil Dra. Matilde Hidalgo de Procel - Veloz Iza, Priscila Jazmin (2020)
The purpose of the case study investigation is to apply the nursing care process in a 19 years old patient with a diagnosis of puerperal sepsis at the Matilde Hidalgo of Procel Maternal and Child Hospital. It was based on obtaining objective and subjective data through caudal assessment, physical and neurological examination of the patient in the nursing care process. Puerperal sepsis is an infectious process that can occur in the puerperium of a woman that affects the entire organism after childbirth, a cessation or by an abortion, could be evidenced the importance that exerts the Nursing staff in the conservation, restoration and self, care of life that is based on the nurse- patient therapeutic relationship.